Technical and political concerns of site remediation: a German case - D´Affonseca, Fernando Mazo; Finkel, Michael (Águas Subterrâneas, 2011)
On a site in Northern Germany the groundwater is contaminated with cyanides. The source is the embankment of a road constructed with slag material in the 70’s. Comprehensive conceptual and mathematical site models were developed to simulate the groundwater flow and the cyanide transport in the aquifer. The calibrated mathematical models were then applied to assess the feasibility of a funnel-and-gate system at the site. Although technically feasible, the decision for this technology was object of political discussion. This case study shows how technical, economical and social aspects have to be properly taken into consideration in clean-up projects.